Dimensi Civic Skill Dan Civic Value Dalam PembelajaranPkn Analisis Isi Buku Ajar Ppkn Serta PelaksanaannyaDi SMA Muhammadiyah 1 Sragen Tahun Pelajaran2015/2016 - Prihastari, Annisa; , Drs. Achmad Muthali'in, M.Si (2016)
This study aimed to describe the dimensions of cargo civic skills and civic values in civic education textbooks and their implementation in SMA Muhammadiyah 1 Sragen in the academic year 2015/2016. This study used a qualitative approach. This study uses data source books Citizenship Education Class XI, the principal, vice-principal areas of curriculum, PPKn teachers, and students. Collecting data using interviews, observation, and study documents or archives. The validity of the data using triangulation of data sources and triangulation techniques. The research method used the analytical techniques of interactive and non-interactive analysis. The results of this study indicate that, textbook PPKn load the civic dimension of skill. Payload civic dimension of skill in the book was published in the form of content, illustrations, and matter. The material in question includes the ability to create good citizens, to monitor the state administration skills, skills in decision making, social problem-solving skills, skills coalition and manage conflict; Civics textbook contains material dimensions of civic value. The substance of the civic dimension of value in the book was published in the form of content, illustrations, and matter. The material is intended commitments, mastery of religious values, norms and ethics, values of justice, democracy, and freedom of the individual; Implementation of the charge material dimensions of civic skills held in conjunction with the learning process by teachers Civics Civics, but it also held outside the classroom in the school environment; Implementation of the charge material dimensions of civic value held in conjunction with the learning process PPKn by civics teachers, but it also held outside the classroom in a school environment. Implementation dimensional shape civic skills and civic values is the interaction between teachers and students in the school environment, the organization's activities, and follow the competitions outside of school.